Effectiveness of STAD with Digital Bingo Media on High-Order Thinking Skills and Learning Motivation in Middle School Biology - Setyani, Dona Amanda; Billah , Arif (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2024)
The aims of this research are to determine the effectiveness of the STAD learning model assisted by digital bingo media on human excretory system topic of the high-order thinking skills of middle school student and to determine students' learning motivation when using the STAD model assisted by digital bingo media. This research uses quantitative research with true experimental methods. Pretest-Posttest Control Group Design is the design in this research. The results of the research show: (1) Teacher activities in implementing the STAD model are appropriate to syntax, with a 92% accurancy; (2) The results of high-order thinking skills show that posttest scores in the experimental class are higher than those in the control class, namely 74.81 > 67.97. Independent sample T-test results obtained t count > t table, namely 2,220 > 2,000 with a significance of 0.03 < 0.05; (3) Students' learning motivation, as seen from the test percentage, shows 72%, which is included in the high category, so it can be concluded that the use of the Student Teams Achievement Division (STAD) model assisted by digital bingo media is effective for high-order thinking skills and has a positive impact on the learning motivation of second year middle school students in the learning excretory system in humans at MTs Negeri Salatiga in 2023/2024 academic year. Abstrak. Tujuan penelitian ini adalah untuk mengetahui keefektifan model pembelajaran STAD berbantuan media bingo digital pada materi sistem ekskresi manusia terhadap keterampilan berpikir tingkat tinggi siswa sekolah menengah dan untuk mengetahui motivasi belajar siswa pada saat menggunakan model STAD berbantuan media bingo digital. Penelitian ini menggunakan penelitian kuantitatif dengan metode eksperimen sejati. Pretest-Posttest Control Group Design merupakan desain dalam penelitian ini. Hasil penelitian menunjukkan: (1) Aktivitas guru dalam menerapkan model STAD sudah sesuai sintak, dengan akurasi 92%; (2) Hasil keterampilan berpikir tingkat tinggi menunjukkan skor pada kelas eksperimen lebih tinggi dibandingkan dengan kelas kontrol yaitu 74,81 > 67,97. Hasil Uji Independent Sample T-test diperoleh t hitung > t tabel yaitu 2,220 > 2,000 dengan signifikansi 0,03 < 0,05; (3) Motivasi belajar siswa dilihat dari persentase tes menunjukkan 72% termasuk dalam kategori tinggi, sehingga dapat disimpulkan bahwa penggunaan model Student Teams Achievement Division (STAD) berbantuan media bingo digital efektif untuk keterampilan berpikir tingkat tinggi dan berdampak positif terhadap motivasi belajar siswa sekolah menengah tahun kedua pada pembelajaran sistem ekskresi pada manusia di MTs Negeri Salatiga tahun pelajaran 2023/2024